Hubungan Kelelahan dan Ketegangan Emosional dengan Baby Blues pada Ibu Postpartum - Apriani Apriani; Wira Ekdeni Aifa; Rizka Mardiya; Fajar Sari Tanberika (Universitas Muhammadiyah Manado, 2025)
Baby blues is a mild and temporary mood disorder commonly experienced by mothers after childbirth. It is characterized by emotional instability, including sadness, anxiety, irritability, and frequent crying, which may interfere with maternal-infant bonding. This condition is often triggered by a combination of physical and psychological factors, such as hormonal changes, fatigue, and emotional tension. This study aims to examine the relationship between fatigue and emotional tension with the occurrence of baby blues among postpartum mothers at Klinik Pratama Annisa Medika 1. A quantitative research method with a cross-sectional design was employed. A total of 45 postpartum mothers were selected using purposive sampling. Data were collected through structured questionnaires measuring fatigue, emotional tension, and baby blues symptoms. The results were analyzed using the Chi-Square test with a significance level set at p<0.05. The findings indicate a statistically significant relationship between fatigue and the incidence of baby blues (p=0.019), as well as between emotional tension and baby blues (p=0.000). These results suggest that both physical and emotional well-being are crucial factors influencing postpartum mental health. The implications of this study highlight the importance of early identification and management of fatigue and emotional stress in postpartum mothers. Healthcare providers should prioritize psychological support, routine mental health screening, and postpartum education to help prevent the onset of baby blues. Early intervention may improve maternal well-being and promote healthier mother-infant interactions.